Inverse modeling framework for characterizing patient-specific microstructural changes in the pulmonary arteries - Pourmodheji, Reza; Jiang, Zhenxiang; Tossas-Betancourt, Christopher; Figueroa, C. Alberto; Baek, Seungik; Lee, Lik-Chuan (Journal of the mechanical behavior of biomedical materials, 2021)
Microstructural changes in the pulmonary arteries associated with pulmonary arterial hypertension (PAH) is not well understood and characterized in humans. To address this issue, we developed and applied a patient-specific inverse finite element (FE) modeling framework to characterize mechanical and structural changes of the micro-constituents in the proximal pulmonary arteries using in-vivo pressure measurements and magnetic resonance images. The framework was applied using data acquired from a pediatric PAH patient and a heart transplant patient with normal pulmonary arterial pressure, which serves as control. Parameters of a constrained mixture model that are associated with the structure and mechanical properties of elastin, collagen fibers and smooth muscle cells were optimized to fit the patient-specific pressure-diameter responses of the main pulmonary artery. Based on the optimized parameters, individual stress and linearized stiffness resultants of the three tissue constituents, as well as their aggregated values, were estimated in the pulmonary artery. Aggregated stress resultant and stiffness are, respectively, 4.6 and 3.4 times higher in the PAH patient than the control subject. Stress and stiffness resultants of each tissue constituent are also higher in the PAH patient. Specifically, the mean stress resultant is highest in elastin (PAH: 69.96, control: 14.42 kPa-mm), followed by those in smooth muscle cell (PAH: 13.95, control: 4.016 kPa-mm) and collagen fibers (PAH: 13.19, control: 2.908 kPa-mm) in both the PAH patient and the control subject. This result implies that elastin may be the key load-bearing constituent in the pulmonary arteries of the PAH patient and the control subject. •Image-based finite element model is developed to study vascular changes in pulmonary arterial hypertension (PAH) in humans.•Stress and stiffness resultants are estimated for the vascular constituents.•Elastin is the primary load-bearing constituent in the pulmonary arteries.•Total stress and stiffness resultants are higher in the (PAH) patient than in the control subject.